MODERN LANDMARKS IN TEACHING ACADEMIC COURSES OF INFORMATION LEGAL PROFILE - L. E. Botasheva; A. S. Gondarenko (Гуманитарные и юридические исследования)
The article describes the experience of implementing information and legal profile and teaching Media Law and Bachelor in EP structure. The study is based on the curricula of the Law Institute of the North Caucasus Federal University and the teaching materials of the Department of Administrative and Financial Law. The article reveals prospects of legal information specialization. The article claims that «Information Law» course should not be considered optional; it is supposed to be compulsory for bachelor students.